PEMANFAATAN LITERASI DIGITAL DI SD MASJID SYUHADA YOGYAKARTA: PRAKTIK, TANTANGAN, DAN PELUANG DALAM PELAKSANAAN PEMBELAJARAN - Enjelika Hani Pamungkas; Rian Nurizka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe and analyze the use of digital literacy in the implementation of learning at SD Masjid Syuhada Yogyakarta. The focus of the study includes teachers’ abilities in utilizing digital literacy, such as accessing, selecting, understanding, analyzing, verifying, evaluating, organizing, distributing, collaborating, and participating in the use of digital technology during the learning process. In addition, this study also examines the challenges faced by teachers and the solutions implemented. The research was conducted in the 2025/2026 academic year at SD Masjid Syuhada Yogyakarta, located in Kotabaru, Gondokusuman. This study employed a qualitative method with a descriptive approach to provide an in-depth description of the use of digital literacy in learning. Data were collected through observation, interviews, questionnaires, and documentation.The results showed that the use of digital literacy was categorized as very good, with an average percentage score of 95.25%. Teachers utilized various digital media such as laptops and mobile devices to access applications and develop learning materials according to students’ needs. Moreover, teachers were able to select appropriate digital learning resources that align with instructional objectives and students’ characteristics.